2003
DOI: 10.1038/sj.ijo.0802318
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, behavioral, and reproductive factors associated with weight gain in Chinese women

Abstract: OBJECTIVE: To examine whether certain sociodemographic, behavioral, and reproductive factors are associated with an increased weight gain in Chinese women. DESIGN: Baseline survey data, including recalled past weight and measured current weight, from an ongoing prospective cohort study conducted in Shanghai, China. SUBJECTS: The analytical sample included 75 039 nonpregnant women aged 40-70 y. MEASUREMENTS: Statistical associations between certain sociodemographic, behavioral, and reproductive factors and weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 38 publications
6
26
0
Order By: Relevance
“…In our study, a woman whose first birth was at age 17-19 y had a 16% increase in odds of overweight and a 30% increase in odds of obesity, while women whose first birth was 23 y or older were at decreased risk. Age at first birth was inversely related to weight gain among both preand postmenopausal Chinese women 41 and an early first birth was significantly associated with overweight and body fat among postmenopausal women. 9,10 We also detected a significant interaction between age at first birth and smoking status, where current smokers had the lowest risk of ow/ob at any age of first birth compared to never and previous smokers.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, a woman whose first birth was at age 17-19 y had a 16% increase in odds of overweight and a 30% increase in odds of obesity, while women whose first birth was 23 y or older were at decreased risk. Age at first birth was inversely related to weight gain among both preand postmenopausal Chinese women 41 and an early first birth was significantly associated with overweight and body fat among postmenopausal women. 9,10 We also detected a significant interaction between age at first birth and smoking status, where current smokers had the lowest risk of ow/ob at any age of first birth compared to never and previous smokers.…”
Section: Discussionmentioning
confidence: 97%
“…Leaving school after age of 16 was associated with decreased weight gain in both men and women, as also seen in other studies. 39,40 Education, income and occupation are used as indicators of socioeconomic status. A recent review of longitudinal studies showed that among non-blacks in developed countries there was a relatively consistent inverse association between weight gain and occupation, and, to a somewhat lesser degree, education, whereas the association between weight gain and income was inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…46 Our study suggests that age at menarche is also associated with adult weight gain, as reported in other studies. 39,40 The EPIC-Oxford cohort differs from other studies in that it involves subjects who are more health conscious than the general UK population. Using data from the two recent British national diet and nutrition surveys, 47,48 we estimated the mean annual weight gain among persons aged 35-49 in the earlier survey to be approximately 700 g in men and 450 g in women.…”
Section: Discussionmentioning
confidence: 99%
“…19 We conducted additional analyses to investigate whether age modifies the associations between major measures of obesity and risk of CHD (Table 4). Among women aged 55 y or under, although the cardiac events were few, BMI was significantly associated with an increased risk of CHD in a dose-response manner, even after controlling for WHR.…”
Section: Resultsmentioning
confidence: 99%